(untitled) (Bangladesh Journal of Botany, 2021)
Twenty-five genotypes of yardlong bean were planted in the field to determine genotypic variances and correlations among characters related to yield. Analysis of variance revealed a highly significant difference among the genotypes for all traits, indicating the presence of variability. The phenotypic coefficients of variations were found slightly higher than the genotypic coefficients of variations, which suggests that the apparent variation is not only genetic but also influenced by the growing environment. High heritability and a high genetic advance were observed in pod yield per plant, pod weight and the number of pods per plant. Yield/plant was positively and significantly correlated with the number of pods/plant, pod length and the number of seeds/pod. The combination of the high heritability along with high genetic advance provides a clear image of the traits in the selection process reflecting the presence of additive gene action for the expression of these traits and improvement of these characters could be done through selection.